A shotgun marriage: Employment equity and human resource planning - Michèle Boonzaier; Billy Boonzaier (South African Journal of Business Management, 1999)
The current state of human resource planning in South Africa is that many companies conduct virtually no such planning or provide it only for senior managerial positions. Employment equity legislation will, however, force the hand of managers and human resource practitioners in the public and private sectors alike to engage in regular human resource planning. The Employment Equity Act (1998) seeks to address the existing discrepancies in the distribution of jobs, occupations and income amongst South Africans by not only eliminating unfair discrimination in employment, but also making provision for affirmative action measures to promote a diverse and representative workforce. The employment equity audit requires the preparation of a workforce profile and consequent employment equity plan to address discrepancies. The main purpose of human resource planning is to identify future human resource requirements (in terms of numbers, skills, and particular characteristics, inter alia gender, race and disability) and to develop action plans to eliminate any discrepancies between the demand and supply of labour that are forecast. The article presents a comprehensive model of human resource planning, incorporating the practical implications of the Employment Equity Act, as a workable guideline to assist managers in compiling thorough forecasts and action plans in fulfilment of organizational and employment equity requirements.
Keywords: 650